Body Image, Self-Esteem, and Physical Exercise as Determinants of Psychological Well-Being among University Students in Malaysia (Sains Humanika, 2025)
The impact of physical exercise on psychological and health benefits has often been examined in both nonclinical and clinical contexts. Although physical exercise is widely recognized for its physical benefits, its psychological effects on well-being are less well understood. This study explored the relationships between physical exercise, body image, self-esteem, and psychological well-being among university students in Malaysia. Specifically, it examined how active participation in physical exercise influenced body image, self-esteem, and overall well-being. The findings highlighted that acceptance of body image contributes to self-esteem, which is further connected to self-confidence and the development of a realistic attitude towards life. Self-esteem emerged as an important safeguard for personal well-being and a strong indicator of subjective well-being. Data were collected via a self-administered questionnaire from 204 university students across Malaysia, using the International Physical Activity Questionnaire (IPAQ) for physical exercise, the Body Shape Questionnaire (BSQ) for body image, the Rosenberg Self-Esteem Scale, and the General Well-Being Schedule. The results indicated significant correlations between physical exercise and body image, as well as between physical exercise and self-esteem. However, physical exercise did not significantly influence psychological well-being. The findings are discussed with several theoretical and practical implications, alongside limitations and recommendations for future research.
Keywords: Physical exercise, well-being, body image, self-esteem, psychological